Предмет: Алгебра,
автор: Elirin
Переведите многочлен к стандартному виду и найдите его решение
a^3b+a^2b-5ab^2+4a^2b+6ab^2 при a=-1, b=2
1/5x-1/5y^2+3/10x-x+7/9y^2 при x=4, y=3/4
Ответы
Автор ответа:
0
1)аb(а^2+a-5b+4a+6b)=ab(a^2+5a+b)=-2(1+(-5)+2)=-2(-2)=4
2)(1/5x+3/10x)-(1/5y^2-7/9y^2)-x=1/2x-(-26/45y^2)-x=2+26/45*(4/3)^2-4=-2+83.2=-81.2
2)(1/5x+3/10x)-(1/5y^2-7/9y^2)-x=1/2x-(-26/45y^2)-x=2+26/45*(4/3)^2-4=-2+83.2=-81.2
Похожие вопросы
Предмет: Физика,
автор: 5annushka
Предмет: Математика,
автор: yeganeimanov17
Предмет: Химия,
автор: bogdanuspesnyj118
Предмет: Математика,
автор: lera10121